Training Scenario Development on Environmental Education Using The STSE Model to Improve Positive Attitudes of Prospective Early Childhood Education Teachers towards The Environment - Muazar Habibi, MA (Early Childhood Research Journal (ECRJ), 2022)
The purpose of this research is to develop training scenarios on environmental education using Science, Technology, Society, Environment (STSE) model integrated into scientific thematic lessons, particularly for prospective early childhood teachers. In addition, product efficiency on the positive attitudes of the trainers towards the environment was examined. The above-mentioned objectives are possibly achieved with the following activities: 1) initializing the Borg Gall model (1999) and 2) assessing the resulting product value using t-test, termed pre-test and post-test. Therefore, the applied simulations were declared suitable for use after series of  developmental events.The results involved three expert assessments in the field of early childhood, environmental education, and educational technology, although further analysis is required. Subsequent investigation conducted on the subject user group, indicating a positive value of 83.3%, in support of the product.Therefore, the efficiency test results showed the training on environmental education using the STSE model and integrated with scientific thematic lessons, were known to enhance 32.44% of all aspects of the prospective teacher's positive attitudes on the environment.